2010
DOI: 10.4314/ijest.v2i5.60098
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on feasibility of recurrence quantification analysis for detecting flank wear in face milling

Abstract: Flank wear is a critical phenomenon which has direct impact on quality of surface finish, dimensional precision and ultimately cost of the finished product. In any metal cutting operation, cutting tool wear estimation will help in identifying tool state, which is a critical factor in productivity. In this paper, the vibration signals are used for detecting flank wear in face milling .The vibration signals are analyzed using a novel non linear technique called recurrence quantification analysis (RQA). RQA inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In paper [7], the feasibility of RQA to detect flank wear in face milling has been investigated. Both qualitative and quantitative approaches were used in order to detect tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [7], the feasibility of RQA to detect flank wear in face milling has been investigated. Both qualitative and quantitative approaches were used in order to detect tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…That may be caused by using a combination of several measures in this model and the combination can reduce the error generated by using only one measure. Meanwhile, we introduced our tree two non-linear measures (TTV and TTA) which are able to evaluate the complexity of a dynamic system, because TT represents the average time in which the system is trapped in a specific state [9]. In our selected decision tree, the root node (in the level 1) is S (node 1) and the nodes in the level 2 are S (node 3) and TTA (node 2).…”
Section: Discussionmentioning
confidence: 99%
“…Hsueh and Yang [15] used the SVM technique in prediction of breakage in face milling cutter using cutting force signals. Mhalsekar et al [25] investigated the vibration signals during face milling using recurrence quantification analysis (RQA) for monitoring the flank wear of tool insert. They concluded that RQA parameters such as entropy, percent laminarity, trapping time and percent recurrence are useful features for detecting the tool flank wear.…”
Section: Introductionmentioning
confidence: 99%